Effect of black soldier fly larva meal on energy, protein digestibility, performance, and carcass quality in local crossbred chickens - Yulianti, Dyah Lestari; Sjofjan, Osfar; Firmansyah, Angga; Ahzami, Abdurahhman; Aini, Baiq Widya Rahmatul (Jurnal Ilmu Peternakan Terapan, 2024)
This research aims to determine the effects of Black Soldier Larva (BSF) meal on metabolic energy, protein digestibility, production performance, characteristics, and carcass quality of local crossbred chickens. The material for this research was 100 local crossbred chickens (the result of crossing male Kampung chickens with female laying hens) aged 30-35 days. The average initial body weight of chickens was 340.6 grams with a coefficient of variation of 5.24%. The research feed is a commercial feed for the finishing period. The experiment involved four treatment groups, where BSF larva meal was incorporated into the feed at levels of 0% (P0), 5% (P1), 10% (P2), and 15% (P3). The experimental design was a completely randomized design with four treatments and five replications. The research variables were metabolic energy, protein digestibility, feed consumption, body weight gain, feed conversion ratio, carcass percentage, and carcass quality. The data were subjected to an analysis of variance, and the differences between groups were determined by Duncan’s test. Based on statistical analysis, BSF Larva meal influences breast muscle weight, meat protein content, apparent metabolic digestibility, and N retention. It can be concluded that BSF larva meal can replace 10% of complete feed without reducing production performance.